On Nonlinear Neutral Fractional Integrodifferential Inclusions with Infinite Delay - Fang Li; Ti-Jun Xiao; Hong-Kun Xu (Journal of Applied Mathematics)
Of concern is a class of nonlinear neutral fractional integrodifferential inclusions with infinite delay in Banach spaces. A theorem about the existence of mild solutions to the fractional integrodifferential inclusions is obtained based on Martelli’s fixed point theorem. An example is given to illustrate the existence result.